A data-driven procedure to determine the bunching window: An application to the Netherlands - Vincent Dekker; Kristina Strohmaier; Nicole Bosch (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
This paper presents new empirical evidence on taxpayers' responsiveness to taxation by estimating the compensated elasticity of taxable income with respect to the net-of-tax rate in the Netherlands. Applying the bunching approach introduced by Saez (2010), we find small, but clear evidence of bunching behaviour at the thresholds of the Dutch tax schedule with a precise estimated elasticity of 0.023 at the upper threshold. In line with the literature, we find much larger estimates for women and self-employed individuals, but we can also identify significant bunching behaviour for wage employed individuals which we can attribute to tax deductions for couples. We add to the bunching literature by proposing to rely on the information criteria to determine the counterfactual model, as well as developing an intuitive, data-driven procedure to determine the bunching window.
urn:nbn:de:bsz:100-opus-12276
Keywords: H21; H24; 330; Elasticity of Taxable Income; Optimal Bunching Window